(untitled) (Journal of Parents and Teachers, 2013)
This section is dedicated to the kinesthetic intelligence, the fifth intelligence inside the multiple intelligences theory. The author makes a definition of this intelligence posting four basic components: corporal expression, manipulative learning, manual ability, fine motor skills and physical and sports exercises. Then he presents different phases in the development of this intelligence. Finally he provides some examples of activities to develop this intelligence particularly or throughout different areas.